2008
DOI: 10.1149/1.2943227
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Reduction on PtFe/C Electrocatalysts Prepared in Microemulsions

Abstract: PtFe/C nanocatalysts of different compositions and nearly constant particle size were prepared by a microemulsion method. Crystallite sizes and degree of alloying were determined by X-ray diffraction. Particle size and distribution were characterized by transmission electron microscopy and average composition was determined by energy dispersive X-ray analysis. Measurements of electrocatalytic activity for oxygen reduction were done using the rotating disk electrode technique in O2 saturated 0.5 mol L-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…In a previous study of the ORR on PtFe/C catalysts, we tried to establish the effects of iron concentration for catalysts prepared in sodium bis͑2-ethylhexyl͒sulfosuccinate ͑AOT͒/n-heptane/water microemulsions. 42 Even though the results obtained revealed that catalyst composition influences the kinetics of the ORR, the concentrations of Fe in the catalysts were lower than those attempted in the preparation. Aiming to overcome that problem, a study using the pseudoternary AOT + n-butanol/n-heptane/water system ͑at a mass ratio of AOT/n-butanol = 2͒ was recently carried out in our laboratory, 43 and demonstrated that the presence of n-butanol in the microemulsion led to the complete reduction of the Fe ions that allowed for obtaining well-alloyed PtFe nanoparticles with the desired composition, without the need of preparing functionalized surfactants or the use of an inert atmosphere.…”
mentioning
confidence: 87%
“…In a previous study of the ORR on PtFe/C catalysts, we tried to establish the effects of iron concentration for catalysts prepared in sodium bis͑2-ethylhexyl͒sulfosuccinate ͑AOT͒/n-heptane/water microemulsions. 42 Even though the results obtained revealed that catalyst composition influences the kinetics of the ORR, the concentrations of Fe in the catalysts were lower than those attempted in the preparation. Aiming to overcome that problem, a study using the pseudoternary AOT + n-butanol/n-heptane/water system ͑at a mass ratio of AOT/n-butanol = 2͒ was recently carried out in our laboratory, 43 and demonstrated that the presence of n-butanol in the microemulsion led to the complete reduction of the Fe ions that allowed for obtaining well-alloyed PtFe nanoparticles with the desired composition, without the need of preparing functionalized surfactants or the use of an inert atmosphere.…”
mentioning
confidence: 87%